Modalitas Jariah, S.Pd dalam Memenangkan Pemilihan Kepala Desa Serentak Tahun 2022 (Studi: Desa Danau, Kecamatan Nalo Tantan, Kabupaten Merangin) - Miranti Miranti; Suryani Suryani2 (Jurnal Politik dan Pemerintahan Daerah, 2023)
This research is entitled "Jariah S.Pd Modalities, in winning the 2022 Simultaneous Village Head Election" (study of Danau Village, Nalo Tantan District, Merangin Regency). The aim of this research is to explain the modalities of Jariah S.Pd, in Pikades in 2022. Modalities are very necessary for candidates to achieve victory in the political arena in accordance with the theory proposed by researchers, namely the theory according to Pierre Bourdieu that there are three capitals used in the arena of political contestation, namely political capital, economic capital, social capital, cultural capital and symbolic capital. The method used in this research is a qualitative method that uses data collection techniques using interview, observation and documentation techniques. The results of this research found that Jariah has the overall modalities of social, economic, political, cultural and symbolic capital. Based on the research results, there is capital that is more dominantly owned by Jariah S.Pd, namely social capital. Supporting factors gave a good and bad impression to Jariah, S.Pd, this was able to be overcome by Jariah, S.Pd and made him able to sit in the village head's chair. Theoretically, the benefit of the research findings is that it can increase knowledge about modalities for the academic fields of students in the faculties of social sciences and political sciences. Meanwhile, practically this research can produce study material from various interested parties to analyze regional democratic practices in Danau Village, Nalo Tantan District, Merangin Regency